2000
DOI: 10.7547/87507315-90-2-70
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of gait plates in controlling in-toeing symptoms in young children

Abstract: A range of patient-oriented and practitioner-oriented outcomes were used to evaluate the efficacy of "gait plate" shoe inlays in controlling symptoms associated with in-toeing in otherwise healthy children. For 18 in-toeing children, parents completed a preintervention questionnaire. Then, during randomized trials, foot placement angle was measured both with and without gait plate inlays in the children's footwear. After the children had worn the gait plates for 1 month, a simple questionnaire was used to rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…These five studies represent the current best available level of evidence in the non-surgical management of an intoed gait pattern in a pediatric population (level IV – case series). Of note, three studies reported specific subject inclusion and exclusion criteria for their cohorts, whilst only two studies further described the presence of the underlying etiologies of their intoeing cohort 3,7,14,20. A total of four different interventions were reported: a flexible leather counter splint, shoe modifications, gait plates, and an orthotic device with a gait plate extension.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These five studies represent the current best available level of evidence in the non-surgical management of an intoed gait pattern in a pediatric population (level IV – case series). Of note, three studies reported specific subject inclusion and exclusion criteria for their cohorts, whilst only two studies further described the presence of the underlying etiologies of their intoeing cohort 3,7,14,20. A total of four different interventions were reported: a flexible leather counter splint, shoe modifications, gait plates, and an orthotic device with a gait plate extension.…”
Section: Resultsmentioning
confidence: 99%
“…This intoed gait pattern is one of the most common referrals made to a pediatric orthopedic specialist 1–6. Parental concern as to the aesthetics of the child’s gait pattern will primarily drive these referrals 3–5,7–11. Whilst some of these referrals will prove to be the result of a normal growth variant,2,9,14–19 some children will present with a symptomatic intoed gait pattern.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations